The Effects of Learning Climate on Innovative Work Behavior in Digital Start-Up Company - Niluh Zahwa Savitry; Marina Sulastiana; Nurul Yanuarti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Along with the fast development of technology, makes computers, robots, and automatization are usually used in the business. This phenomenon makes the competition quite strict for the digital start-up, which provides services in corporate systems. Therefore, a company, an IT-based company, in particular, requires innovation and development. This research aims to analyze the effect of learning climate on innovative work behavior in digital start-up companies. This research used a simple linear regression method with a measuring instrument, namely The Dimensions of Learning Organization Questionnaire and Innovative Work Behaviour. This research was conducted on 102 employees. The result shows that learning climate affects the innovative work behavior in 51% of employees in the company, and the rest 49% are affected by other variables outside this research.